PREVALENSI KECEMASAN DAN DEPRESI PADA PASIEN HEMODIALISIS DI MASA PANDEMI COVID-19 - Anisha Fitria; Dini Herlina Mutiara; Aty Nurillawaty; Yusrini; Ashar Prima (Jurnal Ilmiah Keperawatan IMELDA, 2022)
Background : Hemodialysis therapy is performed in patients with chronic kidney failure to help reduce symptoms due to decreased kidney function. Hemodialysis in patients with chronic kidney failure carried out in the long term causes psychological effects such as anxiety, fear, and depression. The high level of anxiety and depression will affect the effectiveness of the patient's therapy and treatment process so that it can threaten the patient's life. Objective: To determine the prevalence of anxiety and depression in hemodialysis patients during the COVID-19 pandemic at the Hemodialysis Unit of Anna Medika Pekayon Hospital and Rawalumbu Hospital. Methods: This study used descriptive analytic with a cross sectional design. The study population was hemodialysis patients at the Hemodialysis Unit of Anna Medika Pekayon Hospital and Rawalumbu Hospital, using a consecutive sampling technique with a sample of 99 respondents. Data analysis used univariate analysis. Results: Respondents who experienced normal anxiety were 84.8%, borderline anxiety abnormal 13.1%, abnormal 2.0%. Meanwhile, moderate depression/borderline abnormal was 40.4%, normal was 36.4%, and abnormal was 23.2%. Conclusion: the majority of research respondents experienced normal levels of anxiety and moderate/abnormal borderline depression. Suggestion: